Demystifying Polyneuropathy Recent Advances and New Directions - Bozzetto Ambrosi, Patricia (IntechOpen, 2019)
Knowledge of the structure and function of the complex and interwoven network of nerves is inexhaustible and has not been fully determined. The physiological basis of many neuropathic symptoms continues to pursue experts in this field, and in many of the pathological changes related to neuropathies. In the last few decades, there has been increasing interest in new tools applied to diseases involving nerves of the nervous system, which have changed this state of affairs. Microscopic studies, new quantitative histometric methods, and refined physiologic techniques have already expanded our knowledge of structure and function of nerves and rapidly advancing techniques in the fields of immunology and molecular genetics to clarify entire categories of polyneuropathy. Although polyneuropathy is among the most challenging categories of neurological diseases, effective forms of treatment for polyneuropathy have been introduced during the last few decades. This book intends to provide the reader with a broad overview of polyneuropathy, featuring considerations and diagnostic approaches to patients, specific neuropathic syndromes and new related entities, pathogenic mechanisms, and pathological reactions brought to bear to the therapeutic and new clinical applications. All this is important evidence to support present and future directions in this challenging topic.